Pharmacokinetic-pharmacodynamic analysis to evaluate the effect of moxifloxacin on QT interval prolongation in healthy Korean male subjects - Hong T; Han S; Lee J; Jeon S; Park GJ; Park WS; Lim KS; Chung JY; Yu KS; Yim DS (Dove Medical Press, 2015)
Taegon Hong,1,2 Seunghoon Han,1,2 Jongtae Lee,1,2 Sangil Jeon,1,2 Gab-Jin Park,1,2 Wan-Su Park,1,2 Kyoung Soo Lim,3 Jae-Yong Chung,4 Kyung-Sang Yu,3 Dong-Seok Yim1,2 1Department of Pharmacology, College of Medicine, the Catholic University of Korea, Seoul, Republic of Korea; 2PIPET (Pharmacometrics Institute for Practical Education and Training), the Catholic University of Korea, Seoul, Republic of Korea; 3Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 4Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Bundang Hospital, Seongnam, Republic of Korea Abstract: A single 400 mg dose of moxifloxacin has been the standard positive control for thorough QT (TQT) studies. However, it is not clearly known whether a 400 mg dose is also applicable to TQT studies in Asian subjects, including Koreans. Thus, we aimed to develop a pharmacokinetic (PK)-pharmacodynamic (PD) model for moxifloxacin, to evaluate the time course of its effect on QT intervals in Koreans. Data from three TQT studies of 33 healthy male Korean subjects who received 400 and 800 mg of moxifloxacin and placebo (water) were used. Twelve-lead electrocardiograms were taken for 2 consecutive days: 1 day to record diurnal changes and the next day to record moxifloxacin or placebo effects. Peripheral blood samples were also obtained for PK analysis. The PK-PD data obtained were analyzed using a nonlinear mixed-effects method (NONMEM ver. 7.2). A two-compartment linear model with first-order absorption provided the best description of moxifloxacin PK. Individualized QT interval correction, by heart rate, was performed by a power model, and the circadian variation of QT intervals was described by two mixed-effect cosine functions. The effect of moxifloxacin on QT interval prolongation was well explained by the nonlinear dose-response (Emax) model, and the effect by 800 mg was only slightly greater than that of 400 mg. Although Koreans appeared to be more sensitive to moxifloxacin-induced QT prolongation than were Caucasians, the PK-PD model developed suggests that a 400 mg dose of moxifloxacin is also applicable to QT studies in Korean subjects. Keywords: thorough QT study, PK-PD model, NONMEM, Emax model